Are leases substitutes or complements to debt? Insights from an analysis of debt covenants. Issue 3 (20th June 2020) - Paik, Daniel Gyung; Van Der Laan Smith, Joyce; Lee, Brandon Byunghwan; Yoon, Sung Wook
Abstract : Purpose: The purpose of this study is to investigate the relationship between off-balance-sheet (OBS) operating leases and long-term debt by analyzing firms' debt risk profiles measured by the constraints on firms in the financial ratios in their debt covenants. Design/methodology/approach: This study determines debt risk profiles using three measures: the ex ante probability of covenant violation (Demerjian and Owens, 2016), firms in violation of debt covenants and firms close to covenant violations. Findings: High-risk firms according to all three measures, on average, have a significantly lower level of operating leases, indicating that these firms use OBS leases as a substitute for long-term debt. Interestingly, for firms operating in industries in which leases are widely available, firms with a high probability of covenant violation have a significantly higher level of operating leases, indicating that these firms use OBS leases as a complement to long-term debt. Further analysis indicates that lease financing is less costly than debt financing for these firms. Research limitations/implications: Overall, evidence of this study indicates that firms facing financial constraints may attempt to lease more of their assets, but the availability of leasing is constrained by their debt covenant obligations and the strength of the leasing market in its industry. Originality/value: This study identifies states in which risky firms may treat leases as either complements or substitutes for long-term debt, implying that the leasing decision relates to the availability of an active leasing market for a firm's assets and the firm's financial constraints. The findings of this study support recent research showing that debt and leases are complementary in the presence of counterparty risk providing insight into the paradoxical relationship identified in prior research between leases and long-term debt.